Role of olfaction and vision in homing behaviour of black rockfish Sebastes inermis - Mitamura, Hiromichi; Arai, Nobuaki; Sakamoto, Wataru; Mitsunaga, Yasushi; Tanaka, Hideji; Mukai, Yukinori; Nakamura, Kenji; Sasaki, Masato; Yoneda, Yoshihiro (Elsevier, 2005)
How fish find their original habitat and natal home remains an unsolved riddle of animal behaviour. Despite extensive efforts to study the homing behaviour of diadromous fish, relatively little attention has been paid to that of non-diadromous marine fish. Among these, most rockfish of the genus Sebastes exhibit homing ability and/or a strong fidelity to their habitats. However, how these rockfish detect the homeward direction has not been clarified. The goal of the present research was to investigate the sensory mechanisms involved in the homing behaviour of the black rockfish Sebastes inermis, using acoustic telemetry. Vision-blocked or olfactory-ablated rockfish were released in natural waters and their homing behaviours compared with those of intact or control individuals. Blind rockfish showed homing from both inside and outside their habitat. The time taken by blind fish to reach their home habitat was not significantly different from that of the control fish. In contrast, most olfactory-ablated fish did not successfully reach their original habitat. Our results indicate that black rockfish predominantly use the olfactory sense in their homing behaviour.